Implementasi Kebijakan Sistem Akuntabilitas Kinerja Instansi Pemerintah (SAKIP) Pada Sekretariat Daerah Kota Surabaya - Wardhana, Muhammad Fiqih Samudera; T, Tauran (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Performance reporting through the Government Agency Performance Accountability System (SAKIP) represents the responsibility of government agencies to the central government for their annual performance achievements. In accordance with Peraturan Presiden Republik Indonesia No. 29 Tahun 2014, all government agencies, including regional apparatus, are required to implement this system. The implementation is based on strategic planning outlined in the regulation and further reinforced by Peraturan Menteri PAN-RB No. 88 Tahun 2021. Evaluations are conducted to assess the overall execution of the system. This study examines the implementation of SAKIP at the Regional Secretariat of Surabaya City in the context of performance reporting. The research adopts Edward III’s implementation model, which emphasizes four key variables: communication, resources, disposition, and bureaucratic structure. A descriptive qualitative method is used, with data collected through interviews, observations, and documentation to provide a comprehensive analysis. Findings indicate that effective communication plays a crucial role in ensuring successful implementation according to established targets. Additionally, resources such as human resource involvement, availability of facilities, and authority significantly impact execution. Disposition, including understanding, commitment, and a positive attitude toward policy, also contributes to success. A well-structured bureaucracy, supported by clear Standard Operating Procedures, facilitates compliance with regulations. However, challenges persist, particularly in the completeness of information presentation, which affects the quality and relevance of performance reporting. This study concludes that successful SAKIP implementation depends on optimal resource management and strong policy commitment. Therefore, improvements in human resource management and policy comprehension are recommended to enhance the effectiveness of SAKIP at the Regional Secretariat of Surabaya City.